2022
DOI: 10.3389/fped.2022.947869
|View full text |Cite
|
Sign up to set email alerts
|

School assets and bullying in Chinese youth: A multiple mediation model of intentional self-regulation and internet gaming disorder

Abstract: Bullying is a severe social problem affecting young people all over the world. Previous studies suggested that engagement in bullying had massive effects on teenagers’ physical and psychological development. It is critical and necessary to investigate the antecedents and underlying mechanisms of this phenomenon among young generations. The present study, based on the positive youth development perspective and the developmental assets theory, attempts to explore the positive factors in the school subsystem that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 107 publications
2
11
0
Order By: Relevance
“…And this finding enriched the previous studies by directly confirming the cumulative effects of 15 positive attributes on cyberbullying (34,35,37) and empirically responded to Schiamberg et al's advocacy (31) to incorporate PYD theory to investigate bullying behaviors. Additionally, this finding echoes the studies of Xiang et al (28) and Gan et al (38) which revealed the cumulative effects of various developmental assets on reducing Chinese adolescents' IGD. And this current finding also expanded the indirect evidence on relation between several positive attributes and IGD, as well as other forms of addiction (41)(42)(43)(44).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…And this finding enriched the previous studies by directly confirming the cumulative effects of 15 positive attributes on cyberbullying (34,35,37) and empirically responded to Schiamberg et al's advocacy (31) to incorporate PYD theory to investigate bullying behaviors. Additionally, this finding echoes the studies of Xiang et al (28) and Gan et al (38) which revealed the cumulative effects of various developmental assets on reducing Chinese adolescents' IGD. And this current finding also expanded the indirect evidence on relation between several positive attributes and IGD, as well as other forms of addiction (41)(42)(43)(44).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, personal resources and several PYD attributes were significantly associated with bullying behaviors among adolescents ( 36 , 37 ). In terms of IGD, previous studies have revealed the protective effects of various developmental assets in reducing Chinese adolescents' IGD ( 28 , 38 ). Besides, resilience, social competence, emotional competence (e.g., emotional intelligence), self-efficacy, and self-determination are negatively associated with IGD in young people ( 39 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mean scores were calculated, with higher scores reflecting a higher risk of IGD. Previous studies have demonstrated that this questionnaire has good reliability and validity among Chinese adolescent samples ( 92 , 108 ). In the current study, the Cronbach's alpha coefficient was 0.83.…”
Section: Methodsmentioning
confidence: 90%
“…Considering that IGD is also an internet use disorder, this study has reason to assume that IGD has a strong association with cyberbullying perpetration in youth. Moreover, previous research has also suggested the mediating effect of IGD between environmental variables and bullying (92). Addictive behaviors (e.g., smartphone addiction) can also exacerbate the effects of parental neglect on cyberbullying perpetration (24).…”
Section: The Mediating Role Of Internet Gaming Disordermentioning
confidence: 98%
See 1 more Smart Citation